An ultrasensitive luteolin electrochemical sensor based on a glass carbon electrode modified using multi-walled carbon nanotube-supported hollow cobalt sulfide (CoSx) polyhedron/graphene quantum dot composites. Issue 12 (18th May 2022) - Zhang, Li; Zhao, Pengcheng; Wang, Chenxi; Wang, Yilin; Yang, Yaqi; Xie, Yixi; Fei, Junjie
Abstract : Fabrication of an electrochemical luteolin sensor composed of multi-walled carbon nanotube-supported hollow cobalt sulfide (CoSx) polyhedrons/graphene quantum dots and its application in actual sample detection. Abstract : Luteolin (LU), belonging to the group of flavonoids with rich biological activities, has attracted considerable attention. Herein, a novel ultrasensitive LU electrochemical sensor based on hollow cobalt sulfide polyhedron–multi-walled carbon nanotube nanocomposites (CoSx–MWCNTs) and graphene quantum dots (GQDs) was proposed. The hollow CoSx polyhedrons derived from ZIF-67 showed excellent electrochemical sensing performance, which was attributed to the abundant surface active sites endowed by the special hollow structure. When detecting LU using the DPV model, the CoSx–MWCNTs/GQDs/GCE showed a linear range of 5 nM–2000 nM under optimal conditions, and the corresponding detection limit (LOD) was 1.2 nM (S/N = 3). In addition, the sensor exhibited satisfactory sensitivity and accuracy for detecting LU in real samples from Chrysanthemum extracts.